Determinants of health-related quality of life among human immunodeficiency virus positive (HIV-positive) patients at Ahmadu Bello University teaching hospital, Zaria, Nigeria- 2015 - Bello Abdullahi Suleiman; Mohammed Yahaya; F. A. Olaniyan; A. G. Sule; M. B. Sufiyan (BMC, 2020)
Abstract Background The advent of Highly Active Antiretroviral Therapy (HAART) is associated with improved clinical and laboratory outcomes resulting in prolonged life and well-being of people living with Human Immunodeficiency Virus (PLHIV). However, the needs for life-long therapy, medications' side effects and stigma have raised concerns about their quality of life (QOL). This study assessed the determinants of Health-related quality of life (HRQOL) among HIV-positive patients at Ahmadu Bello University Teaching Hospital (ABUTH) Zaria. Methods We conducted a cross-sectional study of 353 HIV-positive adults on HAART attending the HIV clinic of ABUTH, Zaria. The participants were recruited into the study using a systematic sampling technique. Data on socio-demographics, medical parameters, QOL and family functionality were collected using structured, interviewer-administered questionnaire. The World Health Organization (WHO) Quality of Life HIV short form instrument (WHOQOL-HIV BREF) item and Family APGAR tool were respectively used in assessing the QOL and family functionality of the participants. We performed univariate, bivariate and multivariate analysis. Results Mean age was 39.1(±10.9) years, 239 (67.7%) were females, 208 (58.9%) were Hausa-Fulani, 240 (68.2%) married and up to 210 (59.4%) had at least a secondary education. The overall mean scores on the scale of 4-20 for HRQOL were similar in three domains: environment domain 14.5(±2.8); social relationship 14.4(±3.1) and level of independence 14.4(±2.5). Lower scores were recorded in spirituality/religion/personal beliefs 12.3(±4.3). Identified determinants of HRQOL were spousal HIV- positive status (AOR = 3.37; CI; 1.46-7.74) and high family function (AOR = 2.57; CI: 1.51-4.39). Conclusion Having highly functional family and having HIV-positive partner were the major determinants of HRQOL. Routine family counselling and strengthening the HIV social-support network should be incorporated into the routine patients' care in HIV treatment centers.